Adaptive Management: Learning and Action Approaches to Implementing Norms-shifting Interventions - McLarnon, Courtney; Gayles, Jennifer; Deepan, Prabu (USAID / Passages, 2021)
What Passages has Learned about Adaptive Management: • Be reflective about information that is collected and create a culture of learning. • Be systematic about establishing monitoring and learning systems. • Be strategic about data sources and analysis, prioritizing areas for learning and addressing issues raised. • Be inclusive about information collection: who is collecting what, how, and how is it being used.

Value for money and adaptive programming - Approaches, measures and management - Laws, Ed; Valters, Craig (ODI, 2021)
- The United Kingdom’s Foreign, Commonwealth and Development Office (FCDO)’s standard economy, efficiency, effectiveness/cost-effectiveness and equity (4E) framework is still relevant for approaching, measuring and managing value for money (VfM) for adaptive programmes. • However, this framework needs to be reframed to capture and incentivise flexibility, learning and adaptation. • VfM appraisal and reporting should be done in a way that draws on beneficiary feedback and informs good decision-making, rather than just being a compliance exercise. • If VfM appraisal and reporting cannot be done appropriately for adaptive programmes, it should be avoided or minimised. There is a risk of diverting time and resources from more suitable tools and methods.

Learning to adapt & adapting to learn - Using elements of outcome mapping in the ‘Resilient Adolescents in the Syria Crisis’ programme - van Ongevalle, Jan; Kvintradze, Ana; Rennesson, Gaël; Miller, David (Save the Children, 2021)
This learning paper highlights how elements of outcome mapping were used by Save the Children Sweden in a project (2018-2020) that supports adolescents, affected by the Syria crisis, to become more resilient. The paper first outlines how the spheres of influence framework has been applied to develop an actor focused theory of change. It then describes how progress markers, as an alternative to SMART indicators, were formulated to monitor the programme’s results. The paper also outlines how long lists of progress markers were categorised in a more realistic and practical results framework. The paper then continues to elaborate how outcome journals, qualitative data analysis techniques and regular review meetings and reflection workshops were utilised for data collection, for collective learning among programme stakeholders and for informing planning and programme adjustment. Various practical guidelines and tips on how to implement elements of outcome mapping are provided. The final part of the paper explores to what extent outcome mapping was able to foster several key enablers of adaptive programme management and highlights some of the challenges that programme stakeholders faced. Practical recommendations towards the use of outcome mapping in future programmes are also proposed.

A Systems Framework for International Development: The Data-Layered Causal Loop Diagram - Blair, Courtney; Gralla, Erica; Wetmore, Finley; Goentzel, Jarrod; Peters, Megan (Production and Operations Management, 2021)
Meeting the United Nations Sustainable Development Goals (SDGs) will require adapting or redirecting a variety of very complex global and local human systems. It is essential that development scholars and practitioners have tools to understand the dynamics of these systems and the key drivers of their behavior, such as barriers to progress and leverage points for driving sustainable change. System dynamics tools are well suited to address this challenge, but they must first be adapted for the data-poor and fragmented environment of development work. Our key contribution is to extend the causal loop diagram (CLD) with a data layer that describes the status of and change in each variable based on available data. By testing dynamic hypotheses against the system's actual behavior, it enables analysis of a system's dynamics and behavioral drivers without simulation. The data-layered CLD was developed through a 4-year engagement with USAID/Uganda. Its contributions are illustrated through an application to agricultural financing in Uganda. Our analysis identified a lack of demand for agricultural loans as a major barrier to broadening agricultural financing, partially refuting an existing hypothesis that access to credit was the main constraint. Our work extends system dynamics theory to meet the challenges of this practice environment, enabling analysis of the complex dynamics that are crucial to achieving the SDGs.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/poms.13492

Applying Systems Thinking to Education: The RISE Systems Framework - Spivack, Marla (Research on Improving Systems of Education (RISE), 2021)
Many education systems in low- and middle-income countries are experiencing a learning crisis. Many efforts to address this crisis do not account for the system features of education, meaning that they fail to consider the ways that interactions and feedback loops produce outcomes. Thinking through the feedback relationships that produce the education system can be challenging. The RISE Education Systems Framework, which is sufficiently structured to give boundaries to the analysis but sufficiently flexible to be adapted to multiple scenarios, can be helpful. The RISE Framework identifies four key relationships in an education system: politics, compact, management, and voice and choice; and five features that can be used to describe these relationships: delegation, finance, information, support, and motivation. This Framework can be a useful approach for characterising the key actors and interactions in the education system, thinking through how these interactions produce systems outcomes, and identifying ways to intervene that can shift the system towards better outcomes.

Lessons learned from PERL and partners' response to the COVID-19 crisis - Sharp, Samuel; Nwachukwu, Tochukwu; Srivatsa, Sripriya Iyengar (PERL Programme, 2021)
The first case of COVID-19 in Nigeria was confirmed on 27 February 2020, with the first lockdown orders issued on 30 March 2020. The pandemic and resultant containment measures have had farreaching socio-cultural, economic, financial and political implications, globally as well as in Nigeria. For the Partnership to Engage, Reform and Learn (PERL) and its partners, the pandemic has required considerable adaptation of their strategic approach and working practices. This report reflects on how COVID-19 changed the operating context for PERL’s partners, how PERL responded and what lessons have been learned across delivery teams. For government partners, the most substantial impacts have been to budgets, struck by falling oil prices and reduced economic activity. Universally, states have had to adjust budgets and reforecast, revising budgets downwards and shifting the focus of expenditure towards healthcare. The World Bank’s State Fiscal Transparency, Accountability and Sustainability (SFTAS) Programme has generated powerful incentives for this budget revision, which PERL has been able to work alongside. A range of new governance structures – such as public response committees and task forces – have been established to deal with various aspects of COVID-19 policy, and PERL has had to grapple to maintain its ongoing engagement with these. For civil society organisations (CSOs), the closure of offices from 30 March 2020 has changed the nature of engagement with government. CSOs often developed innovative approaches to maintaining access, including use of social media and direct calls. But the shift to virtual working has been challenging for many CSOs, both in terms of covering the costs of data for virtual meetings and the risks of disengagement and marginalisation for some organisations. In response to this changed context, from March 2020 PERL began to restrategise. The flexible nature of the programme’s workplans, progress markers and budgets enabled activities to be adjusted in a relatively timely manner, with a new workplan approved by the end of April 2020. Central PERL management developed a COVID-19 response strategy which provided a broad framework for adaptations, but allowed substantial autonomy to state and regional teams to lead on reprioritisation according to their understanding of the local context. This was valued by both management and delivery staff. Challenges manifested themselves more in effectively delivering on these adapted workplans than in the process of restrategising – due to two rounds of budget cuts, the merger of DFID and the FCO to form the Foreign, Commonwealth and Development Office (FCDO) and the difficulties of engaging partners virtually. Overall, the pandemic undoubtedly delayed activities (by roughly three months for deprioritised areas of work), but resulted in an array of new, tailored interventions under its broad categories of work. Interventions relating to the health sector became more prevalent, as did work supporting budget adjustments. Domestic resource mobilisation and education interventions were often adjusted to be more relevant to the COVID context or experienced delay. The report provides short illustrative case studies of PERL’s adaptations to: support budget revisions; work with media partners on COVID-19 sensitisation; tracking and advocacy for palliative distribution; and support for the introduction of tax relief. There is some evidence, albeit partial, that PERL was able to take advantage of windows of opportunity offered by the pandemic to drive ahead with certain ongoing reform initiatives.

Pushing boundaries: Advocacy evaluation and real-time learning in an HIV prevention research advocacy coalition in sub-Saharan Africa - Dasmariñas, Jules; Schlangen, Rhonda (New Directions for Evaluation, 2021)
Evaluation processes that facilitate learning among advocates must be nimble, creative, and meaningful while transcending putative performance and accountability management. This article describes the experience, lessons, and trajectory of one such approach, Simple, Participatory Assessment of Real Change (SPARC), that a transnational HIV prevention research advocacy coalition pilot-tested in sub-Saharan Africa. Inspired by the pioneering work of the outcome harvesting (OH) and participatory evaluation community, we recuperate advocates' centrality as storytellers, sense-makers, and strategists in advocacy evaluation and describe how we recalibrated SPARC to meet their evaluation and learning needs. This article highlights the normative value of deliberative discourse in evaluation as it contributes to the interpretation of OH and the enrichment of the theory and practice of advocacy evaluation.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/ev.20474